Influence of Sintering Temperature on Phase Formation and Superconducting Properties of Bi2Sr2CaCu2O8+δ via Thermal Treatment Method - Khaidir , Rahayu Emilia Mohamed; Kamarudin, Aliah Nursyahirah; Awang Kechik, Mohd Mustafa; Kien, Chen Soo; Pah, Lim Kean; Shabdin, Muhammad Kashfi; Karim, Muhammad Khalis Abdul; Doyan, Aris; Shaari, Abdul Halim (Journal of Material Science and Radiation, 2025)
High-temperature superconductor Bi2Sr2CaCu2O8+δ (Bi-2212) was successfully prepared using a thermal treatment method, starting with nitrate-based precursors. This study focused on how different sintering temperatures affect the material’s critical temperature, Tc. The process began with a pre-calcination step at 600 °C for 12 hours, followed by calcination at 820 °C for 24 hours. After that, the powder was pressed into pellets and sintered at 830 °C, 840 °C, 850 °C, and 860 °C, each for 24 hours. The Tc-onset values increased with sintering temperature, reaching 50 K at 830 °C, 65 K at 840 °C, and 78 K at 850 °C. SEM images showed closely packed, flake-like grains around 2 μm in size, while XRD analysis confirmed that the sample sintered at 850 °C had the highest Bi-2212 phases as a major phase. Thus, this work outlines the practical steps of the thermal treatment approach and shows how adjusting the sintering temperature can significantly influence the superconducting performance and phase formation of Bi-2212